Di-n-butyl{4-hydroxy-N `-[(2-oxido-1-naphthyl-kappa O)methylene]benzohydrazidato-kappa O-2,N `}tin(IV) - Abu Affan, M.; Sam, N.; Ahmad, F.; Ng, S.W. (International Union of Crystallography, 2010)
The deprotonated Schiff base ligand in the title compound, [Sn(C4H9)(2)(C18H12N2O3)],O,N,O'-chelates to the Sn atom, which is five-coordinated in a cis-C2NO2Sn trigonal-bipyramidal environment. The apical sites are occupied by the O atoms [O-Sn-O = 155.2 (2)degrees]. The hydroxy group is a hydrogen-bond donor to the two-coordinate N atom of an adjacent molecule, the hydrogen-bonding interaction giving rise to a helical chain running along the c axis. The carbon atoms of the butyl chains are equally disordered over two positions.